Pocket-sized hand-held ultrasound for evaluating pediatric functional constipation by both novice and expert clinicians - Waissman, Pola; Berant, Ron; Amir, Lisa; Reif, Shimon; Springer, Shmuel (Frontiers in Pediatrics, 2025)
Background/ObjectivesPediatric functional constipation (PFC) is a global health concern. This study evaluates the utility of pocket-sized ultrasound (PsUS) as a tool for assessing PFC among clinicians with varying levels of ultrasound (US) experience. We assessed the validity of PsUS in measuring transverse rectal diameter (TRD) and rectal anterior wall thickness (RAWT) compared to conventional US and to evaluate agreement between expert and novice clinicians.MethodsIn this cross-sectional study, TRD and RAWT were measured using conventional US and PsUS in 52 children (PFC: n = 28; non-constipated: n = 24), aged 4–14 years. Measurements were performed by an experienced and a novice clinician. Agreement and validity were assessed using intraclass correlation coefficients (ICCs), and diagnostic accuracy was evaluated using receiver operating characteristic (ROC) analysis.ResultsHigh agreement was found between the experienced and novice clinicians in assessing PFC using conventional US (ICC for TRD = 0.98, 95% CI: 0.98–0.99; ICC for RAWT = 0.98, 95% CI: 0.97–0.99) and PsUS (ICC for TRD = 0.99, 95% CI: 0.97–0.99; ICC for RAWT = 0.97, 95% CI: 0.96–0.98). PsUS showed robust validity compared to conventional US (ICCs of 0.96 for TRD and 0.87 for RAWT). ROC analysis showed high diagnostic accuracy for PsUS at TRD [area under the curve (AUC) = 0.88, cut-off 30.25 mm] and RAWT (AUC = 0.91, cut-off 2.05 mm).ConclusionsThese results suggest PsUS is a valid and reliable tool for assessing PFC, that can be used by clinicians with varying levels of US experience.